Pelatihan Kewirausahaan dengan Pendekatan Diskusi Interaktif untuk Menguatkan Motivasi Usaha Mahasiswa - A. Muhammad Idkhan; Iswahyudi Indra Putra; Irawan, I Putu Redy; Dennis Lorens; Nur Fadillah (Lembaga Pengembangan Kinerja Dosen, 2025)
Entrepreneurship training is crucial for enhancing students' understanding and motivation in facing the evolving business world. This community service activity aims to strengthen students' entrepreneurial knowledge and motivation through interactive discussions and business practice simulations. The methods used included pre- and post-tests to measure changes in knowledge and motivation among 30 participating students. The results showed a significant improvement in the cognitive aspect, with the average student knowledge score increasing from 3.5 to 8.3. Furthermore, the motivational aspect also experienced a significant increase, from an average of 25.43 to 43.36, indicating a positive impact of the applied learning model. Overall, this training proved effective in improving students' readiness to understand business concepts and fostering an internal drive for entrepreneurship. Therefore, the interactive discussion model is recommended as a strategy for strengthening entrepreneurship in higher education environments, to provide practical experience while simultaneously increasing students' motivation for entrepreneurship.